Combined Radionuclide Circulation and Static Imaging of the Brain - Kempi, V.; Ritter, B.; von Schéele, C. (Nuklearmedizin - NuclearMedicine, 1980)
Combined static and dynamic imaging of the brain was performed in 398 patients with suspected space occupying lesions. The imaging findings were analyzed from two points of view: Firstly, the radionuclide results were compared with pathological anatomical findings and, secondly, the diagnostic yield in patients with various symptoms was evaluated. Thus we obtained the number of false positive and false negative results. The findings of the combined imaging procedure were correctly negative in 85% of the patients with non-focal symptoms and false positive in only 1%. The circulation study alone gave false positive results in 7% and so did the static study alone. The combined imaging procedure was pathologic in 46 of 83 cases of space-occupying lesions (55%). There were only three patients in whom a pathologic circulation study was the only indication of a space-occupying lesion (4%). The static study alone gave correct positive findings in 23 more cases (28%). We conclude that a pathologic blood flow study alone is of limited interest. In the presence of a pathologic static study the circulation procedure gives additional information, especially in meningioma and subdural hematoma. In patients with symptoms indicative of supratentorial space- occupying lesions of the brain combined imaging is recommended.